THE ISSUE OF MOTOR PARK WITH CHANGE PARAMETERS MATERIAL FLOW - , А. С., А. В. (Municipal economy of cities (Technical science), 2013)
The question of management of fleet for transportation of goods to intercity given temperature. The influence of ambient temperature on the selection of the type of vehicle. The variants forming fleet.